Determinants of Information System Success in the Public Sector: The Moderating Role of Management Support, Tax Complexity, and Locus of Control - Suryaningrum, Diah Hari; Saraswati, Pipit Dwi (PT Global Digital Sains Tekno, 2026)
Purpose: This study aims to examine and analyze the influence of user participation in information system development on system success. Furthermore, it evaluates the role of three contingency factors—top management support, task complexity, and locus of control—as moderating variables influencing this relationship in the context of public services in Indonesia. Method: The research employs a quantitative approach focusing on employees of the tax service office in Malang Regency. A sample of 50 respondents was selected using a simple random sampling technique via the Slovin method. Data were collected through questionnaires and analyzed using Moderated Regression Analysis (MRA) and subgroup analysis to determine the type of moderating variables. Findings: The findings indicate that user participation has a significant positive relationship with information system success. All three contingency factors (management support, task complexity, and locus of control) were proven to act as quasi-moderators. Specifically, high management support and an internal locus of control strengthen the relationship between participation and system success. However, unlike previous studies, lower task complexity showed a greater influence on the relationship in this specific study. Implication: Practically, public sector managers should consider situational factors and individual characteristics before involving users in system development. User participation is not the sole determinant of success; active top management support and an understanding of employees' self-control orientation are crucial for ensuring effective information system implementation to improve public service. Originality: This study provides empirical evidence on the implementation of New Public Management in Indonesia, particularly within tax service offices. The novelty lies in the finding that task complexity in certain public sector organizations may exhibit different influence patterns on IT success compared to the private sector or organizations in other countries.